Integrating Literacy Gardens with the Coffee Value Chain to Promote Sustainable Knowledge Innovation - Maspul, Kurniawan Arif (Jurnal Indragiri Penelitian Multidisiplin, 2024)
The study explores the use of literacy gardens in coffee shops as a novel strategy for promoting intellectual development, sustainability, and community participation in Indonesian cities. These integrated places have the potential to significantly alter urban surroundings by combining coffee shops' cultural appeal and popularity with the transformative power of literacy and sustainability. Literacy gardens at coffee shops promote intellectual development and lifetime learning by creating immersive environments in which people may interact with various reading materials. These venues encourage consumers to continuously learn, think critically, and act curious. Furthermore, incorporating sustainable techniques into literacy gardens encourages responsible consumption and environmental knowledge. Coffee shops can be models of urban sustainability by procuring ethically produced local coffee beans, lobbying for fair trade, and implementing environmentally friendly practices. Literacy gardens at coffee shops promote community engagement and social cohesiveness by functioning as cultural hubs for book clubs, literary discussions, and community events. These integrated venues help to promote cultural variety, heritage preservation, and identity reinforcement by highlighting local literature, folklore, and linguistic resources. The incorporation of literacy gardens into coffee shops provides a revolutionary platform for creating knowledge-driven communities, promoting sustainability, and shaping resilient, inclusive cities. Visionary initiatives, such as Anies Baswedan's ambition to create 40 Indonesian cities, illustrate the potential for positive transformation in urban environments by integrating literacy gardens into the coffee value chain.